2008
DOI: 10.1088/0963-0252/17/1/015017
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of an atmospheric pressure argon glow discharge in a coaxial electrode geometry

Abstract: An atmospheric glow discharge controlled by a dielectric barrier is realized in a coaxial electrode geometry in argon. The discharge characteristics are studied by the electrical method and optical emission spectroscopy. The experimental results indicate that there is only one discharge pulse per half cycle when the applied voltage is very low, and the rise time of the discharge pulses at the positive half cycle is much shorter than that at the negative one. With an increase in applied voltage, the width of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 22 publications
2
30
0
Order By: Relevance
“…[17][18][19] However, the cylindrical configurations of co-axial systems adds an asymmetry due to the difference in surface areas of the electrodes and this has been shown to affect the discharge characteristics. The discharge behaviour is also modified when the dielectric barrier layer is covering just one of the electrodes.…”
Section: Model Descriptionmentioning
confidence: 99%
See 2 more Smart Citations
“…[17][18][19] However, the cylindrical configurations of co-axial systems adds an asymmetry due to the difference in surface areas of the electrodes and this has been shown to affect the discharge characteristics. The discharge behaviour is also modified when the dielectric barrier layer is covering just one of the electrodes.…”
Section: Model Descriptionmentioning
confidence: 99%
“…This trend is also in accordance with the previously reported literature in a co-axial electrode configuration. 2,17 A higher current corresponds to a stronger discharge, which would translate in better decomposition efficiency of pollutants. The trends obtained for discharge current as a function of applied voltage magnitude and frequency are consistent with the experimental results of Du et al, 40 who studied the NOx removal from diesel exhaust using co-axial DBD and observed that the removal rate of NOx first increased and then decreased with increasing the magnitude and frequency of the voltage.…”
Section: -4mentioning
confidence: 99%
See 1 more Smart Citation
“…Ozakazi et al [15] presented the generation of a homogeneous DBD in a 2-mm Ar gap by using a 50-Hz power supply to excite wire mesh electrodes. Radu et al [16] and Dong et al [17] used 10-and 20-kHz power supplies to excite plane-parallel electrodes to generate homogeneous DBDs in 0.3-and 1.5-mm Ar gaps, respectively, and Li et al [18] generated a homogeneous DBD in a 3-mm Ar gap between coaxial electrodes using a 50-kHz power supply. By employing a radio-frequency power supply excitation, homogeneous DBDs in Ar between two plane-parallel electrodes in 1-, 2-, 4-, and 5.5-mm gaps were generated in [19], [20], [21], and [22], respectively.…”
Section: Generation Of Homogeneous Atmospheric-pressurementioning
confidence: 99%
“…[6][7][8][9] Occasionally, under certain conditions, the single period discharge may display an asymmetric discharge mode with different positive and negative current pulses. [10][11][12] Recently, more complex temporal nonlinear behaviors of APGD, such as period-doubling bifurcation and chaos, have been frequently observed in both experiments and numerical simulations. [13][14][15][16][17][18][19] Different from the single period discharge, the current pulses in period-doubling and chaos discharges repeat at multiple applied voltage cycles or fluctuate stochastically.…”
Section: Introductionmentioning
confidence: 99%